2013
DOI: 10.1002/met.1411
|View full text |Cite
|
Sign up to set email alerts
|

An inter‐comparison of Kalpana‐1 and Meteosat‐7 atmospheric motion vectors against radiosonde winds and NWP forecasts during monsoon 2011

Abstract: Geostationary satellites, Kalpana-1 (74 • E) and • E) have overlapping spatial coverage over the Indian region. In this study, the atmospheric motion vectors (AMVs) derived from the above two satellites were compared separately with respect to in situ radiosonde (RS) winds and short-range numerical weather prediction (NWP) forecasts from the National Centre for Medium Range Weather Forecasting's (NCMRWF) T574L64 Global modelling system in terms of statistical parameters vis., speed bias and root mean square v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…RMSD is more below 5 km and less above 5 km than the RMSD in the Mie‐cloudy winds in the respective layers. Validation of AMVs against the short‐term forecasts also showed similar values of RMSD (Rani and Das Gupta, 2013; Sharma et al ., 2021). Le Marshall et al .…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…RMSD is more below 5 km and less above 5 km than the RMSD in the Mie‐cloudy winds in the respective layers. Validation of AMVs against the short‐term forecasts also showed similar values of RMSD (Rani and Das Gupta, 2013; Sharma et al ., 2021). Le Marshall et al .…”
Section: Resultsmentioning
confidence: 65%
“…RMSD is more below 5 km and less above 5 km than the RMSD in the Mie-cloudy winds in the respective layers. Validation of AMVs against the short-term forecasts also showed similar values of RMSD (Rani and Das Gupta, 2013;Sharma et al, 2021). Le Marshall et al (2002) reported that the difference wind threshold, the mean wind difference between AMV and the model equivalent, is situation dependent, near a jet stream or low-level jet, etc., and is typically between 5 and 7 m⋅s −1 , and in general, the difference wind threshold should be less than 10 m⋅s −1 to be considered for assimilation.…”
Section: Nwp Model Backgroundmentioning
confidence: 64%
“…We hypothesized that the satellite wind measurements assimilated in this region could be biased. Previous work has documented upper-level wind speed biases associated with Meteosat-7 over the Southern Hemisphere extending into the higher latitudes (Rani and Das Gupta 2014;Lean and Bormann 2018). Since satellite observations are the only observations at the upper levels in outer portions of the domain, this could degrade the analyses and lead to poor forecasts produced by A-DART.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown the benefit of assimilating AMVs on improving the weather forecasts over the tropics (eg., Velden et al 1992;Leslie et al 1998;Soden et al 2001;Rani and Gupta 2014;Mounika et al 2018). A study by Kaur et al (2015) during the Indian summer monsoon (ISM) reported a positive impact of Kalpana-1 AMV assimilation over the tropical region in the 3DVAR DA system.…”
Section: Introductionmentioning
confidence: 99%